Journal Of Indonesia Economy & Bisnis = Jurnal Ekonomi & Bisnis Indonesia - Budy P. Resosudarmo (Faculty of Economic & Business Universitas Gadjah Mada, 2009)
NO. Penulis --- Judul Artikel --- Halaman 1. Budy P. Resosudarmo, Ditya A, Nurdianto, & Djoni Hartono --- The Indonesian Inter-Regional Social Accounting Matrix for Fiscal Decentralisation Analysis --- 145-162 2. Widigdo Sukarman --- The Politics of Banking : Globalisation and Domestic Policy Change --- 163-176 3. Willy Abdillah --- The Effects Dispositional and Situasional Cogitive Factors on the Intention to Use Internet : An Empirical Study of the Acceptance of Information Technology at Universitas Bengkulu --- 177-204 4. Amiluhur Soeroso & Y. Sri Susilo --- The Strategy of Rural Tourism Development (An Eco-economy and Eco-cultural Approach) --- --- 205-220 5. Ahmad Zafarullah Abdul Jalil --- The Importance of Precautionary Saving Motive among Indonesian Households --- 221-231 6. Lina --- The Effect of Nasty and Non-Nasty Married Celebrity Endorsers on the Attitude, Brand, and Purchasing Intention of the Consumer --- 232-248 7. Rinaningsih --- The Influence of Corporate Governance Practice towards Credit and Bond Yields --- 249-265 8. Sigit Budi Nugroho --- Factors Influencing the Changes of Forest Cover (A Case Study on Sumatra Island) --- 266-280